The engagement of Visegrad countries in EU-Africa relations - Oskar J. Chmiel (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The Czech Republic, Hungary, Poland, and Slovakia, commonly referred to as the Visegrad Four (V4) states, developed friendly relations with several African states both during and after the wave of independence. After the transition from Socialist to democratic systems at the beginning of the 1990s, the focus of the Visegrad countries had shifted to the West. The foreign policies of the V4 mainly focused on the accession to NATO and then to the EU, to the relative neglect of other aspects and regions, including Africa. As one of the conditions for acceding to the European Union (EU) in 2004, the members of the Visegrad group acceded to the EU-Africa, Caribbean, and Pacific Group of States (ACP) Cotonou Partnership Agreement. They also became part of the regular Africa-EU Summits of Heads of State and Government, and became influential actors in the EU's Neighbourhood Policy that covers relations with North Africa as well as with the Central and East European region under the Eastern Partnership (EaP). Discussions on EU-Africa relations strongly emphasise the engagement and interests of certain (founding) EU member states who have traditionally been vocal in this sphere. On the other side, there is a widely spread perception of the V4's lack of interest in Africa. Nevertheless, while facing the recent turmoil induced by the migration crisis, the V4 governments often declare the intention of greater commitment to development cooperation and humanitarian aid, especially in African migrants' countries of origin. This paper discusses the recent engagement of the Visegrad countries in the EU-Africa relations, with a key focus on four main issues (the post-Cotonou mandate negotiations; the southern dimension of the European Neighbourhood Policy; the EU Emergency Trust Fund for Africa; and the European Development Fund). Furthermore, it identifies prospects for the Group's future engagement. The Visegrad countries' foreign policy, as well as economic priorities, primarily lie somewhere else and not in Africa. Their focus on the EaP is one of the reasons why the V4 engagement in the shaping of EU-Africa relations has been limited. Since their interests are elsewhere, they try to balance the EU's focus within its external relations. Also, the V4 countries often point to their lack of interests and expertise in this region. Seemingly, there are too many technical and political limitations for a considerable increase of the V4 engagement in Africa in the near future. This paper's findings suggest that the migration crisis indeed reinforced the increasing interest of Visegrad countries in Africa, and to some extent accelerated their engagement – both in this region and in the EU arena. However, the tendency to (re)engage in Africa had been initiated before the migration crisis, and it was a result of higher interest stemming from security concerns and from the desire to diversify economic ties. The overall conclusion of this paper is that the V4 have not managed to effectively translate their joint positions on EU-Africa relations into collective action within the EU. In most of the cases they did not share interests and, in consequence, did not formulate joint positions. This could particularly be observed in the post-Cotonou mandate negotiations. Nevertheless, along with the emergence of the current migration and refugee crisis, a new field for joint engagement of the V4 appeared. Since joint efforts could help to overcome the lack of capacities for greater development cooperation and diplomatic representation, there is now potential for the Visegrad countries cooperation on the ground.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik